Identifying Immuno-Dominant and Neutralizing Epitopes from K88 Fimbriae of Enterotoxigenic Escherichia coli (ETEC) - T. Lu; W. Zhang (Kansas Agricultural Experiment Station Research Reports, 2017)
Enterotoxigenic Escherichia coli (ETEC) bacteria are the primary cause of diarrheal disease, especially porcine post-weaning diarrhea (PWD). Post-weaning diarrhea is one of the most common diseases in piglets 3 to 10 days after weaning and causes the loss of millions of dollars annually to United States swine industry and other countries. These ETEC bacteria produce two types of virulence factors: 1) fimbriae adhesins, which promote bacterial attachment and colonization in pig small intestine; and 2) enterotoxins that disrupt fluid homeostasis and cause fluid hype-secretion and watery diarrhea. The F4 (K88) is the most important fimbria in ETEC bacteria causing PWD. An effective vaccine against PWD would have to induce antibody responses against the K88 fimbriae. In this study, wein silicoidentified epitopes from the K88 fimbriae of ETEC that are associated with pig neonatal diarrhea and PWD. We genetically fused each epitope to non-homologous human ETEC CFA/I adhesin subunit CfaB to present each K88 fimbrial major subunit FaeG epitope, and examined each fusion protein with anti-K88 antiserum to identify immunodominant epitopes. Furthermore, each epitope fusion was used to immunize mice. Mouse serum samples were titrated for IgG antibody response specific to K88 fimbriae. Mouse serum samples were further examined for antibody neutralization activity against adherence of K88 fimbriae using porcine cell lines IPEC-J2 and porcine ETEC wildtype strain 3030-2. To verify whether epitope conformation alteration could lead to the loss in reacting to anti-K88 serum or in inducing anti-K88 antibody responses, we expressed the FaeG subunit protein and used FaeG protein as the coating antigen in ELISAs and Western Blot to examine antibodies derived from each epitope fusion. Data from this study showed that K88 FaeG epitopes reacted differently to anti-K88 antiserum. Epitopes MTGDFNGSVD, LNDLTNGGTK, GRTKEAFATP, and PMKNAGGTKVGAVKVN showed strong reactivity to anti-K88 fimbria antiserum. Epitope ELRKPDGGTN-induced antibodies were shown strongly neutralizing against adherence of K88+ETEC strain 3030-2 but exhibited a low titer, while epitope FNQAVTTSTQ had a high titer but weak neutralizing ability. Epitopes LGRGGVTSADGEL, PRGSELSAGSA, and RENMEYTDGT were less immunogenic and their derived antibodies showed weak neutralizing activity against K88 fimbria adherence. Interestingly, all mouse serum samples showed strong responses to the FaeG subunit and the denatured K88 fimbriae (not always to the whole K88 fimbriae), indicating some epitopes are located at the adjacent regions of FaeG subunits in assembling to K88 fimbriae. These results indicated epitopes MTGDFNGSVD, LNDLTNGGTK, GRTKEAFATP, and PMKNAGGTKVGAVKVN are immuno-dominant and induced neutralizing antibodies. This study suggests these epitopes are potential antigens for developing precision vaccines against ETEC associated with PWD.
Keywords: epitopes; enterotoxigenic Escherichia coli (ETEC); post-weaning diarrhea (PWD); swine; K88; FaeG